Islamic Moderation in Indonesia in Strengthening the Study of Islamic Community Development (PMI) - Syukur, Abdul; Nugraha, Sugandhi Satria (STAI Miftahul Ula Nganjuk, 2023)
This study aims to analyze the role of Islamic moderation in the context of the development of Islamic Society in Indonesia, with a focus on how this moderation influences views and practices in PMI studies. This research uses a qualitative approach and interview methods as well as text analysis to explore an in-depth understanding of the impact of Islamic moderation in the context of PMI in Indonesia. The research results demonstrate the historical evolution of PMI as a pivotal institution in shaping an inclusive and contextual understanding of Islam in Indonesia. PMI has successfully adapted to various local contexts, promoting religious tolerance and embracing diversity of thought. While it has positively impacted public policy and interfaith harmony, challenges such as radicalization and internet-driven extremism persist. Nonetheless, collaboration with the government, educational institutions, and civil society organizations can further enhance PMI's role in fostering inclusive and tolerant Islamic moderation in Indonesia, promoting social inclusion and reducing tensions among diverse religious understandings. In summary, Islamic moderation is instrumental in advancing PMI studies and enriching cultural diversity and social inclusivity in Indonesia.